Pituitary tumors contain a side population with tumor stem cell-associated characteristics - Mertens, Freya (2015)
Pituitary adenomas cause significant endocrine and mass-related morbidity. Little is known about the mechanisms that underlie pituitary tumor pathogenesis. In the present study, we searched for a side population (SP) in pituitary tumors representing cells with high efflux capacity and potentially enriched for tumor stem cells (TSCs). Human pituitary adenomas contain a SP irrespective of hormonal phenotype. This adenoma SP, as well as the purified SP (pSP) that is depleted from endothelial and immune cells, is enriched for cells that express ‘tumor stemness’ markers and signaling pathways, including epithelial–mesenchymal transition (EMT)-linked factors. Pituitary adenomas were found to contain self-renewing sphere-forming cells, considered to be a property of TSCs. These sphere-initiating cells were recovered in the pSP. Because benign pituitary adenomas do not grow in vitro and have failed to expand in immunodeficient mice, the pituitary tumor cell line AtT20 was further used. We identified a SP in this cell line and found it to be more tumorigenic than the non-SP ‘main population’. Of the two EMT regulatory pathways tested, the inhibition of chemokine (C-X-C motif) receptor 4 (CXCR4) signaling reduced EMT-associated cell motility in vitro as well as xenograft tumor growth, whereas the activation of TGFβ had no effect. The human adenoma pSP also showed upregulated expression of the pituitary stem cell marker SOX2. Pituitaries from dopamine receptor D2 knockout (Drd2−/−) mice that bear prolactinomas contain more pSP, Sox2+, and colony-forming cells than WT glands. In conclusion, we detected a SP in pituitary tumors and identified TSC-associated characteristics. The present study adds new elements to the unraveling of pituitary tumor pathogenesis and may lead to the identification of new therapeutic targets.